EFEKTIVITAS PENDEKATAN MULTIKULTURAL DALAM KONSELING : ANALISIS LITERATUR PADA DINAMIKA LINTAS BUDAYA DI BERBAGAI KONTEKS SOSIAL - Rhahima Zakia; Silvia Netri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research analyzes the effectiveness of the multicultural approach in counseling based on a systematic review of 16 articles. This study focuses on the role of counselors' cultural competence, cultural intelligence, integration of spiritual values, and cross-cultural ethics in enhancing the quality of counseling relationships. The multicultural approach is considered important in creating counseling services that are inclusive and responsive to cultural diversity. The analysis results show that counselors with strong cultural competence can be more effective in supporting client adaptation, building trust, and reducing cross-cultural conflicts. The integration of spiritual values also proves to strengthen the counseling relationship for clients from cultures that highly value spirituality. On the other hand, the cultural intelligence of counselors facilitates a deeper understanding of clients' perspectives, especially in the context of online counseling. Understanding cross-cultural ethics was also found to be essential in building effective communication between counselors and clients, which impacts the creation of a mutually respectful counseling environment. These findings affirm that a multicultural approach in counseling can promote more optimal and harmonious outcomes. This research is expected to serve as a foundation for the development of more effective and diversity-sensitive multicultural counseling practices